Kemampuan Berpikir Kritis dengan menggunakan Model Accelerated Learning (AL) - Rizky Nurul Hafni; Dwi Maulida Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Education helps prepare students to have various abilities and skills that can help them to face and solve real-life problems. One of the skills that every student must possess in order to become a highly qualified human resource is the ability to think critically. The results of the initial research conducted found that out of 30 students who took the critical thinking ability test, only 3 people could answer 2 questions with perfect answers from the 4 questions given. The rest, there are those who answer 1 question, there are even students. Unable to answer all the questions correctly. Students are very difficult to identify the process / mathematical concepts contained in the problem situation given, asked, and check the adequacy of the data, so that students are not able to perform the stages of analysis, evaluation, and inference correctly. This shows that students' critical thinking skills are still low. Whereas critical thinking is one of the important skills to be developed in 21st century learning. This research is a quasi-experimental or quasi-experimental research with a quantitative approach. In this study, the research sample was thirty-five students majoring in science at one Madrasah Aliyah in the city of Medan. To see whether there is an increase in logical thinking ability, a pretest-posttest one group design is used. Then the data that has been collected is analyzed using descriptive statistics. The average critical thinking ability of students increased well. The increase in the mean value of the pretest and posttest does not describe a better ability increase, the n-gain value describes the condition of increasing students' critical thinking skills after receiving TAI learning. The average value of increasing students' critical thinking skills is included in the increase in the high category. Therefore, it was found that the Accelerated Learning (AL) Learning Model can be used as an effort to improve students' mathematical critical thinking skills.